2016
DOI: 10.1111/nep.12557
|View full text |Cite
|
Sign up to set email alerts
|

Association between left ventricular global longitudinal strain, health‐related quality of life and functional capacity in chronic kidney disease patients with preserved ejection fraction

Abstract: GLS was associated with measures of functional capacity and QOL in CKD patients with preserved EF.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
1
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 30 publications
(34 reference statements)
1
5
1
2
Order By: Relevance
“…The novel finding of this study was an association between PCS score and indices of cardiac diastolic (E/A and E/e′) and systolic (GLS) function. Contrary to findings of Krishnasamy et al [16], we found no association between MCS score and GLS. The association between PCS score and echocardiographic markers of cardiac function seems feasible as symptoms of heart failure would limit the daily performance of CKD patients, leading to attenuated QoL.…”
Section: Discussioncontrasting
confidence: 99%
“…The novel finding of this study was an association between PCS score and indices of cardiac diastolic (E/A and E/e′) and systolic (GLS) function. Contrary to findings of Krishnasamy et al [16], we found no association between MCS score and GLS. The association between PCS score and echocardiographic markers of cardiac function seems feasible as symptoms of heart failure would limit the daily performance of CKD patients, leading to attenuated QoL.…”
Section: Discussioncontrasting
confidence: 99%
“…This study found a correlation between percentage reduction of GLS with decreasing distance 6MWT (Table 4). This is in accordance with previous research by Khrisnasamy et al 14 Weak correlation of this result may be due to the many other factors that also affect this 6MWT that may not be in value in this study such as weight, height, patients who have often exercised. Another very important factor that influenced 6MWT especially in cancer patients is psychological motivation and this is not included in this research variable.…”
Section: Discussionsupporting
confidence: 92%
“…12,13 A study conducted by Krishnasamy et al found that there was a correlation between the decrease in GLS and decreased functional capacity assessed by the shortening of 6MWT distance. 14 This study aimed to prove whether there is an association between left ventricular dysfunction in the early stages before there are clinical signs of heart failure examined by using GLS and decreased functional capacity of 6MWT in breast cancer patients receiving anthracycline chemotherapy.…”
Section: Introductionmentioning
confidence: 99%
“…Cardiovascular disease it is the main cause of morbidity and mortality in CKD, with nearly double the incidence of the general population 7 . Moreover, CKD patients with cardiovascular comorbidities have shown progressive worsening in functional capacity 8 . Respiratory complications are also common, such as interstitial pulmonary edema and restrictive spirometric patterns 5 .…”
Section: Introductionmentioning
confidence: 99%